Optimized framework for end-around taxiway design: site, efficiency, fuel: a case study at Jinan Yaoqiang airport - Jiang, Xiaoxi; Yang, Yang (Frontiers in Built Environment, 2025)
IntroductionWith the rapid growth of airport traffic, runway crossings bring about more severe efficiency losses and safety risks. End-Around Taxiways (EATs) have been introduced in some international hub airports, but their design and layout remain contentious.MethodsThis research takes Jinan Yaoqiang International Airport as a case to find the best EATs layout, considering site conditions, operational efficiency, and cost-benefit. First, it sums up EATs classifications and constraints, analyzing the airport’s master plan and site limitations. Then, models for taxiing distance, time, and fuel consumption under different EAT setups are established. Multiple EAT schemes are compared in terms of operation and economy.Results and discussionResults show that a 555-m EAT for Category C aircraft is the best choice for the current construction phase, meeting operations needs while cutting costs and fuel use. In conclusion, EAT design should balance technical requirements with factors like taxiing efficiency, fuel consumption, and investment to achieve airport sustainability. Future studies can optimize EATs via simulation and modeling.